2017
DOI: 10.18267/j.pep.633
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Asymmetries and Nonlinearity of Unemployment and Labour Force Participation Rate in Ukraine

Abstract: With respect to instability and structural changes for maintaining effective functioning of economy an important issue is to study the dynamics of processes in the labour market, including labour supply and employment. Considering negative demographic trends and an acute problem of population aging in Ukraine the article presents an empirical research of the dynamics of labour force participation and unemployment rate, as well as the correlation relationship between them in various periods of time. On the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Some previous research found that the labor force participation as well as other labor market indicators respond distinctive to positive and negative disturbances. Negative shocks have larger and more persisted impact on the change in economic active labor share than positive (Lukianenko and Oliskevych, 2017). Indicated asymmetry in the behavior detects the necessity of nonlinear econometric analysis and development of modern time series models to investigate the economic activity on EU labor market.…”
Section: Data Analysis and Methodologymentioning
confidence: 99%
“…Some previous research found that the labor force participation as well as other labor market indicators respond distinctive to positive and negative disturbances. Negative shocks have larger and more persisted impact on the change in economic active labor share than positive (Lukianenko and Oliskevych, 2017). Indicated asymmetry in the behavior detects the necessity of nonlinear econometric analysis and development of modern time series models to investigate the economic activity on EU labor market.…”
Section: Data Analysis and Methodologymentioning
confidence: 99%
“…There is a large imbalance between the actual education and qualifications of workers and the needs of the labor market (Kasmin, 2014;Lukianenko and Oliskevych, 2017). Despite the fact that Ukraine ranks 7th in the world in terms of the number of citizens with a higher education, 24% of graduates of Ukrainian HEIs can't find a job in the received specialty (Chernaya, 2017).…”
Section: Payment For Studyingmentioning
confidence: 99%
“…The creation of temporary jobs for bachelors who continue to study, according to Lukianenko and Oliskevych (2017), will help to reduce informal (shadow) employment, which in Ukraine reaches 23% of the number of all workers.…”
Section: Workplaces For Studentsmentioning
confidence: 99%
“…Проблемам моделювання міграційних процесів, стану ринку праці, соціально-економічних викликів в умовах в умовах невизначенності та глобалізаційних зрушень присвячено праці відомих українських і західних учених, зокрема В. Гейця. М. Скрипниченко [2], Л. Гур'янової [12], П. Захарченко, Т. Клебанової, О. Черняка [4], І. Лук'яненко, М. Оліскевич [21], Т. Меркулової [7], М. Негрей [9], Ч. Босвела [16] та інших.…”
unclassified